1989
DOI: 10.1111/j.1476-5381.1989.tb14634.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sources of calcium for contraction of the human urinary bladder muscle

Abstract: 1 KC1, carbachol, neurokinin A and endothelin produced concentration-dependent contractions of mucosa-free muscle strips from the dome of the human urinary bladder. The maximal response to carbachol or neurokinin A exceeded that to KCI, while the maximal response to endothelin approached that to KCI.2 Nifedipine (1 gM) abolished the response to KCI, reduced the response to carbachol or neurokinin A but had no effect on the response to endothelin. Bay K 8644 (1 gM) markedly potentiated the response to KCl but h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 36 publications
2
33
0
Order By: Relevance
“…After a further 45 min equilibration period, during which the medium was renewed every 15 min, nifedipine (0.3 mM) was added to the Krebs solution and there was left in all subsequent experimental phases to eliminate spontaneous activity (Maggi et al 1989;Zagorodnyuk et al 1994). After 30 min of incubation in the presence of nifedipine the preparations were challenged with 1 mM [bAla 8 ]NKA(4-10) to evaluate the contractile response of each preparation.…”
Section: Functional Studiesmentioning
confidence: 99%
“…After a further 45 min equilibration period, during which the medium was renewed every 15 min, nifedipine (0.3 mM) was added to the Krebs solution and there was left in all subsequent experimental phases to eliminate spontaneous activity (Maggi et al 1989;Zagorodnyuk et al 1994). After 30 min of incubation in the presence of nifedipine the preparations were challenged with 1 mM [bAla 8 ]NKA(4-10) to evaluate the contractile response of each preparation.…”
Section: Functional Studiesmentioning
confidence: 99%
“…The ET-1-induced contractions were not significantly affected by scopolamine or indomethacin, but could be abolished by incubation in a Ca 2ϩ -free solution, and nifedipine had a marked inhibitory action. On the other hand, in human detrusor, the ET-1-induced contractions were resistant to nifedipine (Maggi et al, 1989d), illustrating species variation in the activation mechanisms. In rabbit bladder, Traish et al (1992) found that ET-1, ET-2, and ET-3 all caused concentration-dependent contractions.…”
Section: Peripheral Targetsmentioning
confidence: 99%
“…ET/SX peptides are also potent contractors of non-vascular smooth muscle preparations such as airways (Battistini et al, 1992;Hay et al, 1993), the urinary bladder (Maggi et al, 1989b;Saenz de Tejada et al, 1992;Traish et al, 1992), the uterus (Bousso-Mittler et al, 1989;Svane et al, 1993; Rae et al, 1993), the stomach fundus (Wood et al, 1992;Warner 1993a), the ileum (Maggi et al, 1989a;Wollberg et al, 1991;Guimaraes & Rae, 1992;Miasiro et al, 1993;Warner et al, 1993b), the colon (Lin & Lee, 1990;Takahashi et al, 1990) and the gall bladder (Maggi et al, 1990; Moummi et al, 1992). To date, two distinct ET receptors (ETA and ETB; Sakurai et al, 1992) have been cloned from mammalian species.…”
Section: Introductionmentioning
confidence: 99%